2013
DOI: 10.2134/agronj2013.0192
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian Ethanol Feedstock Study to Benchmark the Relative Performance of Triticale: I. Agronomics

Abstract: A need has been identified for alternative crop(s) with high grain yield, low grain protein concentration, and high starch for the ethanol industry. The objective of this study was to benchmark the relative performance of triticale (×Triticosecale ssp.) to wheat (Triticum aestivum L.) classes currently utilized for ethanol production. Sixteen cultivars—three triticale, four Canada prairie spring (CPS) wheat, three Canada western soft white spring wheat (CWSWS), two Canada western red spring (CWRS) wheat, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The generally small variance estimates relative to total variance for the random effect of site suggests that rank changes between cultivars, in exclusion of agroecological zone or region interactions, probably were not important. In the first study of this series (Beres et al, 2013), similar observations were reported for agronomic and disease traits with the exception of lodging, which had a site × cultivar variance estimate of 31%. Entry difference variability may increase when the area expands beyond the agroecological zones; however, the area required to observe a response can be large.…”
Section: Discussionsupporting
confidence: 72%
“…The generally small variance estimates relative to total variance for the random effect of site suggests that rank changes between cultivars, in exclusion of agroecological zone or region interactions, probably were not important. In the first study of this series (Beres et al, 2013), similar observations were reported for agronomic and disease traits with the exception of lodging, which had a site × cultivar variance estimate of 31%. Entry difference variability may increase when the area expands beyond the agroecological zones; however, the area required to observe a response can be large.…”
Section: Discussionsupporting
confidence: 72%
“…Larney et al (2017b) reported significantly higher surface residue cover with wheat as the preceding crop (33.7%) compared with narrow-row dry bean (9.7%), which was significantly higher than potato and sugar beet (6.5%-6.7%), which were in turn significantly higher than wide-row bean (3.6%). Beres et al (2013) pointed out that as the bioeconomy evolves, opportunities for dual grain markets have emerged, typified by SWS wheat. A SWS wheat grower can now choose to either sell their wheat into a milling market or contract it to an ethanol plant.…”
Section: Discussionmentioning
confidence: 99%
“…1). However, by 2000, the seeded area of SWS wheat had plummeted dramatically to only 18 000 ha due to low economic returns, changes to consumer dietary preferences, and competition with other wheat classes (Beres et al 2013). McCallum and DePauw (2008) highlighted limited domestic demand as a reason for the decline of CWSWS wheat, with its end-uses filled by soft white winter wheat from Ontario.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starch and protein content in triticale (and traditional crops) are of importance because of the food and feed potential of these crops, therefore if triticale is to substitute many of these crops, it must deliver the same quantity of these components. A recent comparison of triticale and wheat grown under the same conditions showed that the differences in composition between triticale and wheat are small, thanks to new varieties of triticale which have improved composition.…”
Section: Introductionmentioning
confidence: 99%